Optimization of Biodegradable Film from Cellulosa of Seaweed Solid Waste Eucheuma cottonii with Addition of Glycerol, Chitosan, CMC and Tapioca - Sri Hidayati; Zulferiyenni Zulferiyenni; Wisnu Satyajaya (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2019)
Cellulose from the solid waste of seaweed Eucheuma cottonii is one of the wastes that can be used as raw material for making biodegradable films. The condition for making optimum conditions for making biodegradable film from E. cottonii with treatment of glycerol concentration (0; 0,25; 0,5; 0,75; and 1%), tapioca concentration (2; 4; 6; 8; and 10%) , carboxy methyl cellulose (CMC) concentration (1; 2; 3; 4and 5%) and chitosan concentration (1; 2; 3; 4; and 5 The experimental design uses a surface response method with 4 replications. The analysis carried out consisted of elongation percent, tensile strength, solubility and biodegradable film using surface response method. The optimum value occurs in the process conditions using a concentration of glycerol of 0.162%, tapioca concentration of 3.78%, CMC concentration of 2.5% and chitosan concentration of 1.62% with tensile strength 95.013 Mpa, percent elongation of 8.92%, and solubility 80.62%.